Rancang Bangun Meja Kerja Portable Berbasis Ergonomi untuk Meningkatkan Kecepatan Kerja - Gladis Widiandra; Jaka Purnama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Gladbox.co.id is an MSME that makes cake and floral hampers. This business has high mobilityin its production activities but lacks supporting work facilities, resulting in excessive work movements, inefficient production times, and less ergonomic working conditions. These problems have an impact on decreased productivity and work comfort for workers. This study aims to create multifunctional portable work tables and chairs with ergonomic principles based on anthropometric data to improve production process efficiency and work comfort